The Viral Accelerated NF-κB Pathway Probably Drives COVID-19-associated Coagulopathy via Excessive Transcription of Tissue Factor and Plasminogen Activator Inhibitor 1 – Case Report - Leitzke, Marco; Schönknecht, Peter (Archives of Clinical and Biomedical Research, 2021)
Background: The current COVID-19 pandemic creates new clinical challenges almost daily, especially in terms of individual prognoses, diagnostics involving newly discovered pathogenic mechanisms, and the appearance of SARS-CoV-2 mutations. In terms of the thromboembolic complications frequently occurring in COVID-19 patients, there is new evidence that pathognomonic COVID-19- associated coagulopathy (CAC) differs considerably from the coagulant malfunction of common disseminated intravascular coagulation. Thus, bleeding is a rare complication in the initial stages of the disease, whereas thrombotic formations can be seen autopticly in the vasculature of several organs. Therefore, it is speculated that most thromboembolic complications are thrombotic rather than embolic, and CAC is more likely to be a pro-coagulant form of coagulopathy. The reasons for these key differences have remained unknown until very recently. The relationship between SARS-CoV-2 infection and the virus-related acceleration of the transcriptional nuclear factor kappa B (NF-κB)-pathway, with the accompanied excessive down-stream release of NF-κB-dependent proteins, is undisputed. Therefore, the roles of the NF-κB-transcribed anti-fibrinolytic plasminogen activator inhibitor (PAI 1) and NF-κB-dependent tissue factor (TF) have become worthy of attention. Inappropriate TF action results in enhanced fibrin clot formation, whereas overexpression of PAI 1 prevents appropriate fibrinolytic reactions. CAC is interpreted as critically contributing to overall COVID-19 pathology and is most likely an independent risk factor for mortality. Case report: A 49-year-old male patient was admitted for initially non-specific signs of a previously detected SARS-CoV-2 infection. Despite antibiotic and anti-inflammatory, anticoagulant such as respiratory-supporting therapy, respiratory and inflammatory parameters deteriorate